2023
DOI: 10.3389/fendo.2023.1143535
|View full text |Cite
|
Sign up to set email alerts
|

Early changes to retinal structure in patients with diabetic retinopathy as determined by ultrawide swept-source optical coherence tomography-angiography

Yong Zeng,
Miao Liu,
Mengyu Li
et al.

Abstract: PurposeTo investigate retinal vascular changes in patients with diabetic retinopathy (DR) using the newly developed ultrawide rapid scanning swept-source optical coherence tomography angiography (SS-OCTA) device.MethodsThis cross-sectional, observational study enrolled 24 patients (47 eyes) with DR, 45 patients (87 eyes) with diabetes mellitus (DM) without DR, and 36 control subjects (71 eyes). All subjects underwent 24 × 20 mm SS-OCTA examination. Vascular density (VD) and the thickness of the central macula … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Using the newly developed ultra-wide field rapid scanning sweptsource optical coherence tomography angiography (SS-OCTA) device, Zeng et al 48 significant changes in the other regions. In addition, using wide-field OCTA, Xu et al 49 observed that the decrease in retinal vessel density was more marked in peripheral concentric rings with a radius of 0.9-1.2 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the newly developed ultra-wide field rapid scanning sweptsource optical coherence tomography angiography (SS-OCTA) device, Zeng et al 48 significant changes in the other regions. In addition, using wide-field OCTA, Xu et al 49 observed that the decrease in retinal vessel density was more marked in peripheral concentric rings with a radius of 0.9-1.2 cm.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that the total FAZ area does not alter significantly cannot describe the absence of early DR changes. Using the newly developed ultra‐wide field rapid scanning swept‐source optical coherence tomography angiography (SS‐OCTA) device, Zeng et al 48 . had analysed the vessel density in the central macula and five peripheral concentric rings of 1–21 mm in patients with diabetes mellitus without DR.…”
Section: Discussionmentioning
confidence: 99%
“…(A) WF-OCTA (24 × 20 mm) in DR can be used to quantify the vascular morphology at the peripheral retina in patients with DR [27]. Alterations in angio-OCT parameters at the peripheral retina are noted in vascular density and the thickness of vascular capillary WF-OCTA (24 × 20 mm) in DR can be used to quantify the vascular morphology at the peripheral retina in patients with DR [27].…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…Alterations in angio-OCT parameters at the peripheral retina are noted in vascular density and the thickness of vascular capillary WF-OCTA (24 × 20 mm) in DR can be used to quantify the vascular morphology at the peripheral retina in patients with DR [27]. Alterations in angio-OCT parameters at the peripheral retina are noted in vascular density and the thickness of vascular capillary WF-OCTA (24 × 20 mm) in DR can be used to quantify the vascular morphology at the peripheral retina in patients with DR [27]. Alterations in angio-OCT parameters at the peripheral retina are noted in vascular density and the thickness of vascular capillary complexes and can serve as predictors of DR development/progression.…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…This innovative system combines high-speed imaging with an extensive field of view, enabling comprehensive and efficient examination of retinal and choroidal structures [84,85]. An observational study demonstrated that the average vascular density (VD) of the superficial vascular complex (SVC) across all observed areas was significantly lower in DR eyes compared to normal controls [86]. However, only the most peripheral area (16-21 mm) exhibited a significant decrease in VD for the DM group relative to healthy individuals, with a good receiver operating characteristic (ROC) curve value (0.8353) to predict DR.…”
Section: Ultra-wide-field Ss-octa For Vascular Analysismentioning
confidence: 99%